Marketing Strategy Analysis to Increase Sales Volume at PT. XYZ Using the SWOT Analysis Method - Varel Tesalonika Lorencia Agata; Hapzi Ali (Dinasti Publisher, 2025)
This study was conducted at PT. XYZ, an automotive company currently facing heightened market competition. The primary objective of this research is to develop an effective marketing strategy aimed at increasing sales by analyzing both the internal and external conditions of the company. A quantitative descriptive approach was employed, incorporating SWOT analysis alongside the construction of IFAS (Internal Factor Analysis Summary), EFAS (External Factor Analysis Summary), and SPACE (Strategic Position and Action Evaluation) matrices. The SWOT analysis serves to identify strategic elements from both internal and external environments, while the IFAS and EFAS matrices quantitatively assess these factors. The SPACE matrix is utilized to determine the company’s strategic positioning and to formulate the most appropriate strategic direction—whether aggressive, defensive, conservative, or competitive. The findings suggest that the company must leverage its internal strengths and seize external opportunities in order to enhance competitiveness and achieve sustainable sales growth.